"La tua divinità ti eguagliò all'umanità" Efrem il Siro e Nicea - Crimella, Matteo (Teologia, 2025)
The essay analyses some of Ephrem the Syrian's writings that are particularly significant in relation to the Nicene faith. In particular, it focuses on the Hymns on Faith, the Homilies on Faith and the First Homily on Nicomedia. It highlights how Ephrem's system of thought is not philosophical and systematic, but symbolic and evocative. Through paradox, imagery and oppositions, Ephrem shows the richness of the mystery of revelation, which he nevertheless refrains from defining. In particular, in the First Homily on Nicomedia, the Syriac doctor sings of the mystery of Christ's divine-humanity, avoiding any conceptual definition, but showing the richness of the paradoxes of the incarnation of the Son of God and its salvific value that touches human life.